1983
DOI: 10.1007/bf00141072
|View full text |Cite
|
Sign up to set email alerts
|

Tests of a rational theory of the size of government

Abstract: The extensive literature on the size and growth of government attests to the long-standing interest of social scientists in the interrelations of economic development, income distribution, political processes, bureaucracy, and tax rates. Recent surveys of parts of this literature (Peacock, 1979;Cameron, 1978;and Larkey, Stolp and Winer, 1981) show that neither theoretical nor empirical work has resolved the main issues. (See also Peltzman, 1980.) There is little agreement about a common model or framework for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(149 citation statements)
references
References 11 publications
6
142
0
1
Order By: Relevance
“…Finally, especially to explain cross-country differences in public spending, the literature has indicated that, for example, electoral rules (Persson et al 2007), ethnic fragmentation (Alesina et al 1999, Shelton 2007, and income inequality (Meltzer and Richard 1981, 1983, Shelton 2007) are important factors. We refrain from including them as explanatory variables in this study, as they show only limited time variation and, in our model, are therefore already captured by the country-specific fixed effect and time trends.…”
Section: Other Political Influencesmentioning
confidence: 99%
“…Finally, especially to explain cross-country differences in public spending, the literature has indicated that, for example, electoral rules (Persson et al 2007), ethnic fragmentation (Alesina et al 1999, Shelton 2007, and income inequality (Meltzer and Richard 1981, 1983, Shelton 2007) are important factors. We refrain from including them as explanatory variables in this study, as they show only limited time variation and, in our model, are therefore already captured by the country-specific fixed effect and time trends.…”
Section: Other Political Influencesmentioning
confidence: 99%
“…First we show in row 3 the estimates when both the right hand side and left hand side variables are expressed logarithmically, as suggested by Rodrik (1998). Row 4 uses the alternative functional form for redistribution in median voter models that arises out of the classical median voter model of redistribution of Meltzer and Richard (1983), in which the log of the tax rate is a function of the inverse of GDP 21 . The next row turns to the issue of outliers: in order to make sure that our results are not driven by highly influential observations, we exclude all of these observations as measured by the df beta indicator (Besley, Kuh and Welsch, 1980 …”
Section: Single Equation Estimationmentioning
confidence: 99%
“…2 Theories suggesting budget-maximizing bureaucrats, voter myopia, majority voting rules, economic growth, growth of special in terests and many other reasons have been offered as underlying causes of government growth. One of the more commonly studied relations is that of Wagner's Law, or that economic growth is positively related to public sector size; see, for example, Gupta (1967), Bird (1971), Cameron (1978) and Meltzer and Richard (1983). Third, there exists a few studies that attempt to measure the macro-effects of public sector size and growth.…”
Section: Previous Literaturementioning
confidence: 99%